8 - E. C. Amucheazi : Readings in Social Sciences - Issues inBook Reviews: National Development. (Fourth Dimension, 179 Zik Avenue, P.M.B. 1164, Enugu, Nigeria 1980,381 pp.). - system, Journal (Africa Development, 1981)
P. Heinecke, Faculty of Administration, Ahmadu Bello University, Zaria, Nigeria.